Differences in psychomotor abilities among professional and amateur male handball players - Sliz, M; Krupa, R. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
Introduction Handball is a dynamic and fast team sport characterized by high intensity. Therefore reaction and movement time become increasingly important, as also speed of decision-making during handball match situations [1]. Moreover, the ability of quick reaction and correct decision can cause an advantage over the opponent during handball actions [2,3]. This study presents an assessment of the selected psychomotor abilities among professional and amateur male handball players from the Orlen Super league and Central Division. The study included 70 handball players associated in Polish Handball Federation. The main purpose of the paper was to evaluate and compare selected psychomotor abilities of professional and amateur male handball players depending on the position on the court.